Development of a Mathematics Game Illustrated with Jambi Weaving Art to Improve Students’ Critikal Thinking Abilities - Natasya Rahma Sari; Gugun Manosor Simatupang; Novferma (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2026)
This study aimed to develop a mathematics game illustrated with Jambi weaving art on the topic of curved-surface solid geometry to train the critical thinking skills of Grade IX students. The study employed the Research and Development (R&D) method using the ADDIE model, which in this article was limited to the Development stage. The development process included needs analysis, design, and development of an adventure-based game equipped with reasoning problems, clues, and answer explanations. Product quality was evaluated through validation by content experts and media experts, as well as practicality testing by teachers and students. The results indicate that the developed game falls into the highly feasible category, with content expert validation of 93% and media expert validation of 88%, and is categorized as highly practical based on practicality tests by teachers (84%) and students (92.67%). Therefore, the mathematics game illustrated with Jambi weaving art is deemed feasible and practical for use as an interactive and contextual mathematics learning medium.